D.I. Ray. Season two [videorecording (DVD)] - Sondhi, Maya (PBS Distribution, 2024)
"After being suspended from the force when her fiancé was found to have links to organized crime, DI Rachita Ray returns to homicide to investigate another sensitive and high-profile case centering on the murder of Frank Chapman, the head of a notorious crime family, and a local nurse caught in the crossfire. Their deaths ignite tensions across the city, putting DI Ray in a race against time to uncover the truth before the Chapman family act out their revenge and an all-out gang war erupts onto the streets. All evidence points towards a rival crime family, the Mochanis, being responsible for the murders, but as DI Ray starts pulling at the threads of the case, a much more insidious mystery begins to unravel" --Container.